Critical Discourse Analysis On The Representation Of The Orang Asli In The Media: A Comparative Study - Wong, Ka Chun (2023)
Research concerning the representation of the Orang Asli in the media has generally revealed representational patterns that revolve around pejorative and stereotypical depictions. Most of the existing research has mainly examined the community’s representation in mainstream news outlets whereas studies concerning alternative news outlets have received little attention. Thus, this study focuses on examining the representation of the Orang Asli by a comparison between the country’s most frequented mainstream (The Star) and alternative (Malaysiakini) news outlets from a Critical Discourse Analysis (CDA) approach. The news reports were examined using Fairlclough’s (1995b) Three-Dimensional Framework together with the integration of Halliday and Matthiessen’s (2014) Systemic Functional Linguistics (SFL) and van Dijk’s (1998a) Theory of Ideology. A total of 12 news reports were selected from The Star and Malaysiakini respectively and were examined according to the three levels of analysis namely the micro (lexical and transitivity structures), meso (intertextuality), and macro levels (sociocultural practices and ideology) as outlined in Fairclough’s (1995b) framework. The findings at the micro and meso level show that the Orang Asli were portrayed to be traditional, dependent, problematic, and underdeveloped by both news outlets. This study also found that the positive actions of the authorities were emphasised whereas the negative characteristics of the Orang Asli were accentuated thus resulting in the ideological polarisation of “Us versus Them”. However, the findings also revealed that Malaysiakini did represent the voices of the Orang Asli more frequently as compared to The Star.